1983
DOI: 10.1136/oem.40.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and relation to underground exposure of radiological irregular opacities in South Wales coal workers with pneumoconiosis.

Abstract: A total of 124 coal workers and ex-coal workers receiving disability benefit for coal worker's pneumoconiosis and routinely reattending the Cardiff Pneumoconiosis Medical Panel during a 10-week period were studied. Those with complicated pneumoconiosis were excluded. Their current chest radiographs and their chest radiographs at the time of certification were read in random order by three readers using the 1980 ILO Classification of Radiographs. An irregularity score was derived from the readings. The x-ray fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
7
0
4
Order By: Relevance
“…The clinical features of the disease have been described in coal miners. 29,[33][34][35] It is associated with irregular opacities on the chest radiograph, 36,37 diffusion impairment (low DLCO), hypoxemia, and a restrictive pattern on pulmonary function testing. 34,35 It may have clinical, radiological, and functional characteristics mimicking IPF.…”
Section: Pulmonary Fibrosis and Restrictive Impairment Clinical And Pmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical features of the disease have been described in coal miners. 29,[33][34][35] It is associated with irregular opacities on the chest radiograph, 36,37 diffusion impairment (low DLCO), hypoxemia, and a restrictive pattern on pulmonary function testing. 34,35 It may have clinical, radiological, and functional characteristics mimicking IPF.…”
Section: Pulmonary Fibrosis and Restrictive Impairment Clinical And Pmentioning
confidence: 99%
“…[33][34][35] The category of irregular opacities correlates with dust exposure. 36,37 Pathologically the interstitial fibrosis takes two major forms. The most common is a bridging fibrosis between the nodular and macular lesions of CWP or silicosis 29 (Fig.…”
Section: Pulmonary Fibrosis and Restrictive Impairment Clinical And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the presence of either pleural or parenchymal abnormalities cannot be attributed to cigarette smoking alone. While several authors have suggested that smoking is independently associated with small opacities on chest radiograph, [ThCriault et al, 1974;Amandus et al, 1976;Cockcroft et a]., 19831, these studies did not include subjects without dust exposure, precluding the possibility of accurately identifying an independent effect of smoking. In one important investigation of this issue, NIOSH-certified B readers found a prevalence of parenchymal abnormalities (ILO score of 110 or greater) of less than 1% in a large population of blue collar workers with minimal exposure to occupational respiratory hazards [Castellan et al.…”
Section: Discussionmentioning
confidence: 99%
“…irregulär) und Lokalisation der Lungenschatten eine verlässliche Zuordnung zu einem Krankheitsbild, insbesondere der Silikose und Asbestose, möglich ist, lässt sich nach eingehenderen Studien nicht halten. Vielmehr zeigen Untersuchungen insbesondere der Arbeitsgruppe Petsonk [51] und auch anderer Untersucher [52,53], dass praktisch stets rundliche und irreguläre Schatten nebeneinander bestehen und auch deren bevorzugte Lokalisation variieren kann. Diese Heterogenität der radiologisch fassbaren Lungenveränderungen trifft in noch weit größerem Maße für Mischstaub-Pneumokoniosen zu.…”
Section: Diskussionunclassified